Pathophysiological aspects, phenotype and early neurostimulation in patients with microcephaly secondary to Zika Virus - Tavares, Cícera Luana Cruz; Cesário, Bruna Kerolayni Leite; Pinheiro, Isabelly de Oliveira; Filho, José Gilmar Sampaio; Fernandes, Camila Grangeiro; Cruz, Allana Maria Garcia Sampaio (Seven Editora, 2023)
The Zika virus (ZIKAV) is a flavivirus, which causes an arbovirus of epidemiological importance, mainly in tropical countries, which was first isolated in 1947 from a monkey in the Zika forest in Uganda and later in humans in Nigeria. In Brazil, in May 2015, ZIKAV infection was identified, which spread throughout the Americas and coincided with an increase in neurological complications such as congenital microcephaly and numerous cases of Guillain-Barré syndrome, an autoimmune disease that can cause acute flaccid paralysis, areflexia and ascending. Recently, some reports from the Brazilian Ministry of Health showed that cases of congenital microcephaly have increased among newborns in the northeastern region of the country, indicating a probable association with ZIKAV infection during pregnancy. The purpose of this study was to investigate in the literature the pathogenesis of microcephaly caused by ZIKAV and to present the phenotype of newborns affected by prenatal infection, prognosis and results of early neurostimulation of these affected newborns. It was prepared from a literature review in the VHL (Virtual Health Library) and PubMed (Medline) electronic databases. The search for the articles was restricted between 2009 and 2019. A search strategy was developed in Portuguese and English for each of the databases searched, using the following health descriptors: Zika virus, microcephaly and pathogenesis. The descriptors are in accordance with the Medical Subject Headings (MeSH) and Descriptors in Health Sciences (DeCS). Based on the review performed, ZIKAV infection during pregnancy appears to be the cause of a recognizable pattern of congenital anomalies that is consistent and odd, although there are many similar components in other congenital infections there are some distinguishing features, among them severe microcephaly with partially collapsed skull, cerebral cortex with subcortical calcifications, macular scarring and pigmentary retinal spotting, congenital contractures, and early hypertonia with symptoms of extrapyramidal involvement. Based on the phenotype presented by these children, the treatment determined is individualized, and early neurostimulation is essential for better neuronal spasticity and to improve the quality of life of these newborns. DOI:https://doi.org/10.56238/interdiinovationscrese-018